Replicating a Scalable Intervention That Helps Students Reappraise Academic and Social Adversity During the Transition to Middle School. Issue 4 (1st October 2020) - Pyne, Jaymes; Borman, Geoffrey D.
Abstract: Recent evidence suggests that helping students reappraise common social and academic worries during the difficult transition to middle school can improve their academic achievement. To further test this outcome, we conducted a pre-registered randomized controlled trial at scale among students transitioning to middle school in seventh grade (N = 2, 171). The intervention increased students' seventh-grade grade point average, the sole confirmatory outcome proposed in preregistration, and reduced course failures when compared to controlgroup students. Differences in effects between those found for white students and for other racial/ethnic groups were not statistically significant. These results reinforce previous findings suggesting that reappraising stressful school situations during the transition to middle school may improve academic achievement for students across all demographic groups.